Nanostructured Lipid Carrier: A Review - Neha S. Ghogare,; Dr. Vikrant P. Wankhade,; Dr. Shrikant D. Pande,; Dr. Sandeep C. Atram,; Dr. Nishan N. Bobade,; Vikram V. Bhoyar,; Tanvi S. Kokate, (Asian Journal of Pharmaceutical Research and Development, 2025)
Nanostructured Lipid Carriers (NLCs) are nanoscale colloidal systems developed for drug delivery, featuring a core composed of solid and liquid lipids. These lipid-based carriers have emerged as biocompatible, non-toxic, and safer alternatives to polymeric and metallic nanoparticles. Their advantageous properties—such as improved safety, physical stability, and higher drug-loading capacity compared to other lipid-based nanocarriers—have attracted significant interest from researchers aiming to develop efficient and reliable drug delivery systems. NLCs enhance the solubility and permeability of therapeutic agents by encapsulating them within a lipid matrix, making them suitable for administration via challenging biological routes. Furthermore, surface functionalization and the incorporation of specific excipients can enhance targeted delivery and extend systemic circulation. Owing to these features, NLCs hold great potential in the treatment of various conditions, including cancer, infectious diseases, neurodegenerative disorders, hypertension, diabetes, and chronic pain. This review provides a comprehensive analysis of NLCs, focusing on their structural components, fabrication techniques, characterization methods, formulation strategies, and applications in pharmaceutical and therapeutic contexts, particularly in targeted drug delivery systems.